Investment facilitation and India: A closer look - Manu Misra (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2021)
This Perspective considers India's policy towards investment facilitation, both in the domestic context and internationally. It seeks to shed light on potential causal factors underlying India's stance towards related negotiations at the WTO. While acknowledging that some apprehensiveness might be justified, it questions whether total non-participation remains a proportionate response.
Keywords: 330